THE IMPACT OF MACROECONOMIC CHANGES ON THE BUSINESS DECISIONS OF MANAGERS IN AGRICULTURE - Tasic, Vladimir T; Milošević, Isidora (International Journal of Economic Practice and Policy, 2017)
In this paper, the greatest attention was paid to the specific problems faced by managers in agriculture. In order to survive in the market and respond to the challenges that lie ahead of them, they first have to look at the analysis of the macroeconomic environment before making a business decision. Our managers in agriculture should be primarily facing export strategy of agricultural products. As is now self-financing of agricultural production difficult to achieve, managers in agriculture are resorting to alternative sources of funding where it is necessary to find the optimal ratio of own and borrowed capital with the objective of positive operating. In order to efficiently produce and export their products require a state subsidy, given the lack of state support managers in agriculture need to meet the additional capital to bank loans.
Keywords: macroeconomic environment; managers in agriculture; alternative sources of financing; export strategy; equity; borrowed capital